Vasari, sus Dimore (Arezzo y Florencia) y lo Stanzino del Príncipe: Teatro-Memoria-Sapiencia - Suárez Quevedo, Diego (Abaton. Revista de figuración, representación e imágenes de la arquitectura, 2023)
The aim of this article is to focus on and approach the multifaceted figure of Giorgio Vasari from the perspective of the memory-theatre-sapience trinomial, as a means of study that can clarify and provide important clarifications and concatenated and interwoven data regarding his varied activity, from painter, writer and architect to his status as a court artist and consummate craftsman of perspective.
Keywords: Vasari; courtly art; scenography; Renaissance; artist's house